1987
DOI: 10.1007/bf02593873
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery anomalies in tetralogy of fallot

Abstract: Coronary angiograms of 296 patients with Fallot's tetralogy were reviewed. Group I abnormalities in the origin and distribution of the coronary arteries, found in 32 (11.8%) cases, consisted of a single coronary artery from the left sinus of Valsalva in 7 cases, left anterior descending artery from the right coronary artery in 7 cases, and an accessory left anterior descending from the right coronary in 18 cases. Of the 7 cases with a single coronary artery, the right coronary branch was anterior to the aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…Although almost all of cases with complex congenital heart disease are associated with a VSD, this defect offers an effective advantage for transvenous coronary ar- teriography since the coronary artery ostia are located just above the VSD [4, 8,9]. Anatomically more important, the right coronary artery ostium is located at a site close to the VSD and anterior in TOF [7,8,10], making the right coronary catheter insertion easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although almost all of cases with complex congenital heart disease are associated with a VSD, this defect offers an effective advantage for transvenous coronary ar- teriography since the coronary artery ostia are located just above the VSD [4, 8,9]. Anatomically more important, the right coronary artery ostium is located at a site close to the VSD and anterior in TOF [7,8,10], making the right coronary catheter insertion easier.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the right coronary ostium is located just above the margin of the ventricular septal defect (VSD) and the left coronary ostium is located opposite the ventricular septum resulting in the most distant position [4,8,9].…”
Section: Catheter Designmentioning
confidence: 99%
“…[2][3][4] Although the presence of a single coronary artery is usually considered as a benign condition, it has some prognostic implications depending on its origin, distribution, and relation with early atherosclerosis. This is an extremely rare congenital anomaly and is seen in only 0.0024% to 0.044% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] SCA may be associated with other severe congenital cardiac malformations (persistent truncus arteriosus, tetralogy of Fallot, pulmonary atresia). 5,6 The first case of SCA was reported by Thebesius in 1716 and Halperin et al made the first antemortem diagnosis by means of CAG in 1967. 4 The clinical significance of SCA is unknown and although it is generally considered benign, some authors have studied sudden death associated with isolated congenital coronary anomalies in an autopsy population and observed that sudden death occurred in patients with SCA.…”
mentioning
confidence: 99%